Pedicle screw cement augmentation. A mechanical pullout study on different cement augmentation techniques. Issue 2 (February 2016) - Costa, Francesco; Ortolina, Alessandro; Galbusera, Fabio; Cardia, Andrea; Sala, Giuseppe; Ronchi, Franco; Uccelli, Carlo; Grosso, Rossella; Fornari, Maurizio
Highlights: Pedicle screw augmentation with PMMA allows for a significant increase of the pull-out strength of the screws when implanted in osteoporotic bone. The use of cannulated and fenestrated screws did not increase the mechanical pull-out performances of the screw with respect to only retrograde filling. Solid screws with vertebroplasty and retrograde cement filling guaranteed the highest pull-out forces. Abstract: Pedicle screws with polymethyl methacrylate (PMMA) cement augmentation have been shown to significantly improve the fixation strength in a severely osteoporotic spine. However, the efficacy of screw fixation for different cement augmentation techniques remains unknown. This study aimed to determine the difference in pullout strength between different cement augmentation techniques. Uniform synthetic bones simulating severe osteoporosis were used to provide a platform for each augmentation technique. In all cases a polyaxial screw and acrylic cement (PMMA) at medium viscosity were used. Five groups were analyzed: I) only screw without PMMA (control group); II) retrograde cement pre-filling of the tapped area; III) cannulated and fenestrate screw with cement injection through perforation; IV) injection using a standard trocar of PMMA (vertebroplasty) and retrograde pre-filling of the tapped area; V) injection through a fenestrated trocar and retrograde pre-filling of the tapped area. Standard X-rays were taken in order to visualize cement distribution in each group. Pedicle screws at full insertion were then tested for axial pullout failure using a mechanical testing machine. A total of 30 screws were tested. The results of pullout analysis revealed better results of all groups with respect to the control group. In particular the statistical analysis showed a difference of Group V ( p  = 0.001) with respect to all other groups. These results confirm that the cement augmentation grants better results in pullout axial forces. Moreover they suggest better load resistance to axial forces when the distribution of the PMMA is along all the screw combining fenestration and pre-filling augmentation technique.